2019
DOI: 10.1371/journal.pone.0225706
|View full text |Cite
|
Sign up to set email alerts
|

Impact of relational leadership on employees’ unethical pro-organizational behavior: A survey based on tourism companies in four countries

Abstract: Based on the theory of social construction and self-consistency, this study aims to investigate the mechanism of relational leadership’s role in employees’ unethical pro-organizational behavior (UPB) from the perspective of moral identity and ethical climate. We found that relational leadership negatively correlates with the instrumental ethical climate, positively correlates with caring ethical climate, and exerts no significant impact on the rule ethical climate. Instrumental ethical climate and caring ethic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…The first potential explanation involves the nature of these two types of organizational behavior. While organizational fairness and leadership attention are top-down relationships, organizational fairness focuses on institutionalism, whereas leadership attention is based on subjectivity (individual leaders) [ 12 , 15 , 17 , 39 , 40 ]. We argue that this relationship has similarities to the nature of football matches, with organizational fairness being similar to competition rules, and leadership attention being similar to the behavior of the referee.…”
Section: Discussionmentioning
confidence: 99%
“…The first potential explanation involves the nature of these two types of organizational behavior. While organizational fairness and leadership attention are top-down relationships, organizational fairness focuses on institutionalism, whereas leadership attention is based on subjectivity (individual leaders) [ 12 , 15 , 17 , 39 , 40 ]. We argue that this relationship has similarities to the nature of football matches, with organizational fairness being similar to competition rules, and leadership attention being similar to the behavior of the referee.…”
Section: Discussionmentioning
confidence: 99%
“…This approach to the evaluation of leaders is used by many researchers, e.g. Mostafa; Zhang X, Yao Id Z; and Engelbrecht, Heine, Mahembe [29][30][31]. Jaramillo, Carrillat and Locander argue that when individuals evaluate themselves or their performance they are likely to rely on inner thoughts, feelings and personal attributes [32].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research often brought about results that demonstrated the influence of leadership on intensified UPB among the followers [ 13 , 14 , 18 ]. This sometimes happens directly, but more commonly takes place through the agency of other phenomena, including organizational identification [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that leadership can decrease employees’ engagement in UPB [ 15 , 16 ], while others indicate that it contributes to its increase [ 13 , 17 ]. Moreover, numerous studies have concluded that leadership causes employee engagement in UPB to increase through the moderating influence of various factors, such as the ethical climate [ 18 ], continuance commitment [ 19 ], work engagement [ 20 ], moral disengagement [ 21 ], reflective moral attentiveness [ 22 ], and organizational identification [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%